IMPLEMENTASI MODEL PEMBELAJARAN KOMBINASI ANTARA NHT DAN TGT TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS SISWA KELAS XI SMA NEGERI 9 SEMARANG - Miftahurrohman Miftahurrohman; Eko Andy Purnomo (PROSIDING SEMINAR NASIONAL & INTERNASIONAL, 2017)
The low ability of mathematical communication in learning is very important to note, because through mathematical communication studentscan understand the function and purpose of mathematics both orally and inwriting. Number Head Together is a learning model that puts more emphasison student activity in searching, processing, and reporting information fromvarious sources that finally presented in front of class. Teams GamesTournament (TGT) is one type or model of cooperative learning that is easyto apply, involves the activities of all students without having any statusdifference, involving the role of the student as a peer tutor and containingelements of game and reinforcement. The purpose of research to determinethe ability of mathematical communication through learning modelcombination between NHT and TGT. Researchers apply it to students ofclass XI-MIPA6 SMA Negeri 9 Semarang. Type of research is qualitativedescriptive research, which this research focuses on problem of student'smathematical communication ability. The result of data analysis show thatstudents' mathematical communication ability by applying combinationlearning model between Numbered Head Togeter and Team Group ofTurnament in learning Matrix is increasing with marked with quiz prbadi asmany as 29 students from 35 students answered well and correctly on thequiz no 1. Keywords: Komunikasi matematis, NHT, TGT.